Endothelium-restricted endothelin-1 overexpression in type 1 diabetes worsens atherosclerosis and immune cell infiltration via NOX1. Issue 4 (13th June 2020) - Ouerd, Sofiane; Idris-Khodja, Noureddine; Trindade, Michelle; Ferreira, Nathanne S; Berillo, Olga; Coelho, Suellen C; Neves, Mario F; Jandeleit-Dahm, Karin A; Paradis, Pierre; Schiffrin, Ernesto L
Abstract: Aims: NADPH oxidase (NOX) 1 but not NOX4-dependent oxidative stress plays a role in diabetic vascular disease, including atherosclerosis. Endothelin (ET)-1 has been implicated in diabetes-induced vascular complications. We showed that crossing mice overexpressing human ET-1 selectively in endothelium (eET-1) with apolipoprotein E knockout ( Apoe −/− ) mice enhanced high-fat diet-induced atherosclerosis in part by increasing oxidative stress. We tested the hypothesis that ET-1 overexpression in the endothelium would worsen atherosclerosis in type 1 diabetes through a mechanism involving NOX1 but not NOX4. Methods and results: Six-week-old male Apoe − / − and eET-1/ Apoe − / − mice with or without Nox1 ( Nox1 − /y ) or Nox4 knockout ( Nox4 − / − ) were injected intraperitoneally with either vehicle or streptozotocin (55 mg/kg/day) for 5 days to induce type 1 diabetes and were studied 14 weeks later. ET-1 overexpression increased 2.5-fold and five-fold the atherosclerotic lesion area in the aortic sinus and arch of diabetic Apoe − / − mice, respectively. Deletion of Nox1 reduced aortic arch plaque size by 60%; in contrast, Nox4 knockout increased lesion size by 1.5-fold. ET-1 overexpression decreased aortic sinus and arch plaque alpha smooth muscle cell content by ∼35% and ∼50%, respectively, which was blunted by Nox1 but not Nox4 knockout. Reactive oxygen species production was increased two-fold in aortic arch perivascular fat of diabetic eET-1/ Apoe − / − and eET-1/ Apoe −/− / Nox4 −/− mice but not eET-1/ Apoe −/− / Nox1 y/− mice. ET-1 overexpression enhanced monocyte/macrophage and CD3 + T-cell infiltration ∼2.7-fold in the aortic arch perivascular fat of diabetic Apoe − / − mice. Both Nox1 and Nox4 knockout blunted CD3 + T-cell infiltration whereas only Nox1 knockout prevented the monocyte/macrophage infiltration in diabetic eET-1/ Apoe − / − mice. Conclusion: Endothelium ET-1 overexpression enhances the progression of atherosclerosis in type 1 diabetes, perivascular oxidative stress, and inflammation through NOX1. Graphical Abstract: